Videogame as avant-garde – Secluded rhematic expression - Veli-Matti Karhulahti (New Academic Press, 2022)
This article shows how the single player videogame is by its very nature in conflict with the institution of art, and paradoxically, because of that cannot avoid becoming art itself. First, the article shows that the defining aesthetic of the videogame–its kinesthetically charged ludic rhematic–has very little in common with the meaning-centered aesthetic norms that dominate the art world. Second, the article shows how the secluded nature of expressive video- game play contravenes the concept of art reception. These conflicts force art to reinvestigate itself through the videogame. That makes the videogame avant- garde, for a moment.
Context Matters! Exploring and Reframing Games and Play in Context